β-Arrestin 1 in Thyrotropin Receptor Signaling in Bone: Studies in Osteoblast-Like Cells - Boutin, Alisa; Gershengorn, Marvin C.; Neumann, Susanne (Frontiers in Endocrinology, 2020)
A direct action of thyrotropin (TSH, thyroid-stimulating hormone) on bone precursors in humans is controversial. Studies in rodent models have provided conflicting findings. We used preosteoblast-like osteosarcoma-derived U2OS cells engineered to stably overexpress human TSH receptors (TSHRs) as a model of osteoblast precursors (U2OS-TSHR cells) to investigate TSHR-mediated effects in bone differentiation in human cells. We review our findings that 1) TSHR couples to several different G proteins to induce upregulation of genes associated with osteoblast activity – interleukin 11 (IL-11), osteopontin (OPN), and alkaline phosphatase (ALPL) and found that the kinetics of the induction and the G protein-mediated signaling pathways involved were different for these genes; 2) TSH can stimulate β-arrestin-mediated signal transduction and that β-arrestin 1 in part mediates TSH-induced pre-osteoblast differentiation; and 3) TSHR/insulin-like growth factor 1 (IGF1) receptor (IGF1R) synergistically increased OPN secretion by TSH and IGF1 and that this crosstalk was mediated by physical association of these receptors in a signaling complex that uses β-arrestin 1 as a scaffold. These findings were complemented using a novel β-arrestin 1-biased agonist of TSHR. We conclude that TSHR can signal via several transduction pathways leading to differentiation of this model system of human pre-osteoblast cells and, therefore, that TSH can directly regulate these bone cells.